2021
DOI: 10.3390/ijms22062804
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of AP-1 Transcription Factor JunB in Angiogenesis and Vascular Development

Abstract: Blood vessels are essential for the formation and maintenance of almost all functional tissues. They play fundamental roles in the supply of oxygen and nutrition, as well as development and morphogenesis. Vascular endothelial cells are the main factor in blood vessel formation. Recently, research findings showed heterogeneity in vascular endothelial cells in different tissue/organs. Endothelial cells alter their gene expressions depending on their cell fate or angiogenic states of vascular development in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 92 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…Previous studies have reported that the JNK/c-Jun/AP-1 pathway can be regulated via IL-13 in human vascular endothelial cells to participate in vascular inflammation-related pathophysiological alterations [ 54 ]. JUNB plays an important role in the production of vascular endothelial growth factor (VEGF), which induces JUNB expression in the budding vascular adventitia [ 55 57 ]. During mouse development, Junb expression is elevated in vascular endothelial cells owing to neurovascular interactions and is involved in the embryonic vascular network construction [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the JNK/c-Jun/AP-1 pathway can be regulated via IL-13 in human vascular endothelial cells to participate in vascular inflammation-related pathophysiological alterations [ 54 ]. JUNB plays an important role in the production of vascular endothelial growth factor (VEGF), which induces JUNB expression in the budding vascular adventitia [ 55 57 ]. During mouse development, Junb expression is elevated in vascular endothelial cells owing to neurovascular interactions and is involved in the embryonic vascular network construction [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the statement that neurodegenerative mechanisms could be detectable from a peripheral tissue. JUNB, EGR1, NR4A2 belong to immediate-early genes (IEGs) and encode the transcription factors, JunB, Egr-1, NR4A2, respectively [54][55][56][57]. These factors are activated in respond to a variety of cellular stimuli and control specific neuronal functions, including neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 20 different transcription factors that can bind the CLDN9 promoter region with a 100% score were determined. e majority are considered the key regulators of epithelial differentiation and organ development, i.e., CP2 [84], the maintenance of the germline stem cells, i.e., USF [85], enhancers that activate transcriptional programs and cellular reprogramming, i.e., GATA1 and GATA 3 [86], favor cell growth and proliferation, i.e., AP1 and AP4 [87], and facilitate TJ formation in carcinoma cells, i.e., HNF4 [88].…”
Section: Discussionmentioning
confidence: 99%